Content Embedded Literacy in the Workplace - Dârjan, Ioana; Federighi, Paolo; BOFFO, VANNA (Proceedings e report, 2009)
The topic of embedded literacy, closely connected to embedded learning on one hand, and training in the workplace on the other, is a central theme for reflection on adult education in Europe and around the world. The Council of Europe indicates knowledge as a pivotal element for the economic and social development of the EU countries and the workplace is an important place for the learning and production of know-how and knowledge. The problem of achieving the competences needed for entering the current labour market concerns a large part of the adult population. And this is where embedded literacy comes in, a topic which the volume tries to deal with from a twofold viewpoint: through theoretical reflection outlining the theme against the development of the European labour market, and reflection on hands-on experiences resulting from a project financed by the European Community called CELiNE, Content Embedded Literacy Education for the New Economy, carried out between 2007-2009.